Penta Helix Collaboration to Fight Poverty in Tangerang City - Latuconsina, Hudaya; Ahmad; Sofian; Sofia Latif, Inas (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
The phenomenon of poverty is a social problem that is always discussed in a global context. Not only in developing countries, even poverty is still possible in developed countries. Poverty is still one of the government's homework because the achievement of sustainable development targets still requires several efforts to evaluate improvements. Similarly, in Tangerang City, although the poverty rate in this city is not the highest and can be said to be relatively low, it still needs to be considered to be improved. Researchers use qualitative research methods through literature review and focus group discussion (FGD) to collect data. The results show that in fighting poverty, all relevant parties must be involved. Even though cooperation has been established, penta helix coordination still needs to be realized in reality. Researchers suggest the need to regulate and strengthen collaboration between academia, the private sector, society, government and the media who are members of the penta helix. Furthermore, harmonization and synchronization of rules with applied policies should also be carried out. So that all related things can be accommodated properly.